Meningkatkan Kemahiran Penggunaan Tanda Baca Dalam Bahasa Melayu Dengan Menggunakan Teknik Warna Bagi Pelajar Tahun Satu Di Universiti Fatoni - Bukehmatee, Nurnee; Jehwae, Phaosan; Ummah Tohlong, Ummul; Baru, Muhammadzofree (Journal of Information System and Education Development, 2025)
This action research was conducted to help first-year Malay Language Major students in understanding and mastering the use of punctuation marks for capital letters, commas and punctuation in writing Malay sentences. Color technique is used in this study. The study sample in this action study consists of five students who are facing problems with the use of reading marks through the results of the review of exercise books and student activity books. Research data was collected through three types of instruments, namely through structured observation, structured interviews and document analysis. The results of data analysis found that all study participants showed improvement in understanding and mastering the use of punctuation marks for capital letters, commas and full stops. Through the observation instrument, it was found that the study participants showed a high interest and concentration in using color techniques while doing worksheet activities. As for the interview instrument, it shows that the study participants better understand the concept of using three types of reading marks, and are interested in color techniques. The instrument through document analysis also showed that all study participants successfully mastered the use of punctuation marks. Overall, the results of the study show that the use of color techniques can help students to understand and master the use of reading marks effectively